2018
DOI: 10.24218/vjpps.2018.21
|View full text |Cite
|
Sign up to set email alerts
|

Statutory Imposed Terms of Stress, Distress, Well-Being and Animal Welfare: Suggested Guidelines for Humane Endpoints in Animal Studies

Abstract: Bad terminology is the enemy of good science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The highly disadvantageous net effects of the internal factors cannot be compensated anymore with even the most advantageous net effects of the external factors, and the animal will suffer from seriously impaired welfare. Also, this case should prompt those in charge of safeguarding animal welfare to think about, and eventually apply, a humane endpoint (Gauvin et al, 2018).…”
Section: The Dynamic Component In Dawconmentioning
confidence: 99%
“…The highly disadvantageous net effects of the internal factors cannot be compensated anymore with even the most advantageous net effects of the external factors, and the animal will suffer from seriously impaired welfare. Also, this case should prompt those in charge of safeguarding animal welfare to think about, and eventually apply, a humane endpoint (Gauvin et al, 2018).…”
Section: The Dynamic Component In Dawconmentioning
confidence: 99%
“…The International Association for the Study of Pain defined «the pain» as an unpleasant sensory experience along with actual or potential tissue damage. Based on this definition, pain is always subjective (Gauvin et al, 2018).…”
Section: Historical Background Of the Use Of Animals In Biomedical Research And The Guidelines Governing Itmentioning
confidence: 99%
“…Nowadays, researchers have shown that animal suffering leads to the extensive change of biomarkers in the animal body, affecting data obtained from the experiment (Gauvin et al, 2018). Since the results of research are evaluated based on the decreased suffering in the animal, new methods including pre-clinical and non-clinical procedures were introduced for HEP.…”
Section: Ethics In the Implementation Of Humane Endpointsmentioning
confidence: 99%